The Wisdom of Honeybee Defenses Against Environmental Stresses - Li, Guilin; Zhao, Hang; Liu, Zhenguo; Wang, Hongfang; Xu, Baohua; Guo, Xingqi (Frontiers in Microbiology, 2018)
As one of the predominant pollinator, honeybees provide important ecosystem service to crops and wild plants, and generate great economic benefit for humans. Unfortunately, there is clear evidence of recent catastrophic honeybee colony failure in some areas, resulting in markedly negative environmental and economic effects. It has been demonstrated that various environmental stresses, including both abiotic and biotic stresses, functioning singly or synergistically, are the potential drivers of colony collapse. Honeybees can use many defense mechanisms to decrease the damage from environmental stress to some extent. Here, we synthesize and summarize recent advances regarding the effects of environmental stress on honeybees and the wisdom of honeybees to respond to external environmental stress. Furthermore, we provide possible future research directions about the response of honeybees to various form of stressors.